The Characteristics of Megagastropod Abundance in the Seagrass Beds of Malahing Village, Bontang City, East Kalimantan - Mustika, Ananda; Irawan, Aditya; Sari, Lily Inderia (Jurnal Biologi Tropis, 2025)
Megagastropoda are well associated with seagrass ecosystems. Megagastropoda play a role in the food chain in seagrass beds as detritus eaters. The purpose of this study was to analyze the relationship between megagastropoda abundance and seagrass density in the seagrass beds of Malahing Village, Bontang City, East Kalimantan. This study was conducted from October 2024 to February 2025. The sampling stations consisted of 4 stations and each station consisted of 3 sub-stations. Sampling used the purposive sampling method. Megagastropoda and seagrass stand sampling used a 50x50 cm square frame. Water parameter measurements were carried out in situ and ex situ and basic substrate sampling used a corer. Megagastropoda data analysis included abundance, relative abundance of species, diversity index, uniformity and dominance. Seagrass data analysis included density and relative density of species. The relationship between megagastropoda abundance and seagrass density used a Pearson's Product Moment correlation test. Megastropoda found as many as 14 species of megagastropoda namely Strombus urceus, Cypraea tigris, Trochus maculatus, Cymbiola innexa, Nassaridus dorsatus, Polinices tumidus, Rhinoclavis vertagus, Natica vitellus, Vasum turbellinus, Scaphander watsoni, Astralium calcar, Conus sp., Cypraea cervinetta, and Strombus gibberulus, and 2 species of seagrass were found namely Enhalus acoroides and Thalassia hemprichii. The relationship between the abundance of megagastropoda and the density of E. acoroides is very strongly positively correlated.